Anesthesia in Caesarean Section Patients with Hyperthyroid - Matdhika Sakti; Ferianto Ferianto; Dewi Indayani (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Thyrotoxicosis is defined as a state of excess thyroid hormone and is not synonymous with hyperthyroidism, which is the result of excessive thyroid function. The prevalence of hyperthyroidism ranges from 0.2% to 1.3% in iodine-sufficient regions of the world. The combination of increasing FT4 and suppressing TSH is one way to enforce the hyperthyroidism diagnosis. The case of a 22-year-old woman with a diagnosis of G6P3A2H3 premature contractions has been reported , who came to the surgical room at Dr. HOSPITAL. Suhatman MARS to perform a caesarean section. Based on the pre-operative physical examination carried out, it was found that the patient's physical status was ASA II. In this patient, regional anesthesia will be planned. The patient has a history of hyperthyroidism since ± 10 years ago and regularly takes Thyrozol once a day during pregnancy and controls it with a specialist in Internal Medicine. Theoretically, this shows that the suspected condition of the patient is hyperthyroidism and if continued it could lead to Graves' disease, toxic nodular goiter, subclinical hyperthyroidism, or other conditions that lead to hyperthyroidism so surgery must be carried out taking this situation into account.